2018
DOI: 10.1155/2018/3246508
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Project Complexity across Different Industry Sectors

Abstract: Increasing complexity of projects is mentioned as one of the reasons for project failure—still. This paper presents a comparative research to investigate how project complexity was perceived by project practitioners in different industry sectors. Five sectors were included: process industry, construction industry, ICT, high-tech product development, and food processing industry. In total, more than 140 projects were included in the research, hence providing a broad view on Dutch project practice. From the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
1
26
0
3
Order By: Relevance
“…Despite this growth, Bakhshi et al [29] showed that IS project complexity only represents 8% of project complexity research dated to 2015. Furthermore, Bosch-Rekveldt et al [4] was arguably not able to fully articulate IS project complexity as these projects only represented 5.5% (8/144 projects) of their research sample.…”
Section: Information Systems Project Complexitymentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this growth, Bakhshi et al [29] showed that IS project complexity only represents 8% of project complexity research dated to 2015. Furthermore, Bosch-Rekveldt et al [4] was arguably not able to fully articulate IS project complexity as these projects only represented 5.5% (8/144 projects) of their research sample.…”
Section: Information Systems Project Complexitymentioning
confidence: 99%
“…Projects however continue to perform poorly and fail to meet their goals and realise organisational benefits [1,21]. e extant literature contends that a key reason for projects failing is complexity [2][3][4][5].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many external stakeholders participate in mega projects, including but not limited to investors, contractors, governments and suppliers, which will cause social conflicts as a cause of complexity to be occurred. https://doi.org/10.15405/epms.2019.12.6 Corresponding Author: Mohammad Mohseni Selection and peer-review under & Hertogh, 2018;Callegari, Szklo, & Schaeffer, 2018;Dao et al, 2016;Eriksson et al, 2017;Forozandeh, Ebrahim, & Makui, 2018;Hartono, 2018;He, Luo, Hu, & Chan, 2015;Hu et al, 2015;Abdou et al, 2016;Kuhn, Schaefer, & Otten, 2018;Lessard, Sakhrani, & Miller, 2014;Makui, Zadeh, Bagherpour, & Jabbarzadeh, 2018;Maylor & Turner, 2017;Mikkelsen, 2018;Mirza & Ehsan, 2017;Mok, Shen, & Yang, 2015;Mozaffari, Fazli, & Sedaghat-Seresht, 2012;Nguyen et al, Ambiguity in the domain the dynamics of work activities 5 (Bakhshi et al, 2016;Bjorvatn & Wald 2018;Bosch-Rekveldt et al, 2018;Callegari et al, 2018;Dao et al 2016;Eriksson et al 2017;Forozandeh et al, 2018;Habibi, Barzinpour, & Sadjadi, 2018;Hartono 2018;He et al, 2015;Invernizzi, Locatelli, Gronqvis, & Brookes, 2019;Abdou et al, 2016;Kuhn et al, 2018;Lehtinen, Peltokorpi, & Artto, 2019;…”
Section: Step 3 • Review Journals and Top Authorsmentioning
confidence: 99%
“…Number of specializations involved in the project, 4 (Bjorvatn & Wald 2018;Bosch-Rekveldt et al, 2018;Callegari et al, 2018;Dao et al, 2016;Eriksson et al, 2017;Forozandeh et al, 2018;Habibi et al, 2018;Hartono, 2018;He et al, 2015;Hu et al, 2015;Abdou et al, 2016;Kuhn et al, 2018;Lessard et al, 2014;Li et al, 2018;Makui et al, 2018;Maylor & Turner, 2017;Mirza & Ehsan, 2017;Mok et al, 2015;Mozaffari et al, 2012;Nachbagauer & Schirl-Boeck, 2019;Nguyen et al, 2015;Qazi et https://doi.org/10.15405/epms.2019.12.6 Corresponding Author: Mohammad Mohseni Selection and peer-review under 14 al., 2016;Qiu et al, 2019;Rolstadås & Schiefloe 2017;Senescu et al, 2013;Shahhossein et al, 2017;Sheffield et al, 2012;Shi et al 2018;Silva, Akchurin, & Bebbington, 2018;Sridarran et al, 2017;Turner & Xue, 2018;Zhu & Mostafavi, 2017) Common vision of the project team, 3…”
Section: Referred Researchersmentioning
confidence: 99%